2015
DOI: 10.1136/bmjopen-2014-005828
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening and HPV vaccine acceptability among rural and urban women in Kilimanjaro Region, Tanzania

Abstract: ObjectiveTo determine cervical cancer screening coverage and the knowledge, attitudes and barriers toward screening tests among women in rural and urban areas of Tanzania, as well as explore how they view the acceptability of the HPV vaccine and potential barriers to vaccination.SettingA cross-sectional study using interview-administered questionnaires was conducted using multistage random sampling within urban and rural areas in Kilimanjaro Region, Tanzania.ParticipantsWomen aged 18–55 were asked to participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
121
4
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 39 publications
17
121
4
8
Order By: Relevance
“…Reports from suburb area of Thailand found 33% or 35% of 'never had' screening (Kritpetcharat et al, 2003;Wongwatcharanukul et al, 2014). In capital cities of other countries, the rates of 'no screening' varied widely from 15-90% (Claeys et al, 2002;Al Sairafi and Mohamed, 2009;Baskaran et al, 2013;Núñez-Troconis et al, 2013;Cunningham et al, 2015). Aside from the 35% of 'never had' screening, 18% and 4% of Bangkok women had only one test or the last test was more than 5 years, making up 57% of the inadequate screening in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from suburb area of Thailand found 33% or 35% of 'never had' screening (Kritpetcharat et al, 2003;Wongwatcharanukul et al, 2014). In capital cities of other countries, the rates of 'no screening' varied widely from 15-90% (Claeys et al, 2002;Al Sairafi and Mohamed, 2009;Baskaran et al, 2013;Núñez-Troconis et al, 2013;Cunningham et al, 2015). Aside from the 35% of 'never had' screening, 18% and 4% of Bangkok women had only one test or the last test was more than 5 years, making up 57% of the inadequate screening in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the reasons why women did not have cervical cancer screening, reports from many countries had various findings (Tran et al, 2012;Baskaran et al, 2013;Núñez-Troconis et al, 2013;Cunningham et al, 2015). Several basic characteristics of the women may result in various reasons, such as, education, obstetrics and gynecologic history, and familial or cultural background, etc.Studies from South America, Africa and Asia reported that absence of symptoms, no knowledge, lack of time, embarrassment, fear of pain, anxiety on privacy violation and fear of infection, etc.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Kesediaan vaksinasi pada wanita usia produktif di Tanzania 93% dan pada perawat di Nigeria 90%. 1,14 Di Indonesia, 96,1% orang tua bersedia anaknya divaksinasi. 15,16 Para remaja di Yogyakarta beralasan perlu berdis- 10 Persetujuan orang tua adalah hal yang sangat penting.…”
Section: Pembahasanunclassified
“…Namun, informasi yang salah akan menyebabkan persepsi negatif sehingga kesediaan vaksinasi rendah. 1 Penelitian di Spanyol dan Jerman menunjukkan situs laman tentang vaksin HPV sebagai sumber informasi yang sering diakses. Situs laman tersebut memberikan info kurang berimbang tentang kelengkapan, transparansi, dan dimensi infeksi HPV serta vaksinasi HPV.…”
Section: Pembahasanunclassified
See 1 more Smart Citation